Income and financial aid effects on persistence and degree attainment in public colleges - Dowd, Alicia C. (Education Policy Analysis Archives, 2004)
This study examined the distribution of financial aid among financially dependent four-year college students and the effectiveness of different types of financial aid in promoting student persistence and timely bachelor’s degree attainment. The findings of descriptive statistical and logistic regression analyses using the NCES Beginning Postsecondary Students (1990-94) data show that subsidized loans taken in the first year of college have a positive effect on persistence. The first-year distribution of aid does not close the income gap in bachelor’s degree attainment. Living on campus and first-year grade point average are the most important predictors of timely degree completion.